MANAJEMEN PEMBELAJARAN TEACHING FACTORY DALAM MENINGKATKAN KOMPETENSI KEAHLIAN SISWA DI SEKOLAH MENENGAH KEJURUAN (SMK) - Putra, Dino Adi; Vratiwi, Septiana; Hidayatullah, Riski Randa; Hasan, Taufik Abdul (Jurnal Manajemen Pendidikan, 2022)
This study aims to determine teaching factory management in terms of planning, organizing, implementing, monitoring, and evaluating as well as knowing the supporting and inhibiting factors of teaching factory management in Vocational Schools in an effort to develop the quality of learning. This research is a qualitative research in which data collection techniques include interviews, observation and documentation analysis. Data analysis techniques used descriptive qualitative analysis including data collection, data reduction, data display and data verification. The results of this study state that the management of the teaching factory at SMK N 1 Painan in terms of planning has been carried out properly such as administering time, tools and practicum materials at the workshop and organizing the teaching factory which is well structured starting from the head of competency skills, the head of labor, the teacher subjects and implementation have been carried out properly with supervision carried out integrated by all components of the school. And then the supporting factors include: competent teachers, supporting facilities and infrastructure, enthusiastic students, toolmen, block system practice schedules, and collaboration with DUDI, the inhibiting factors are less than optimal time, marketing and a less strategic place. As well as the results of implementing teaching factory management, it provides the provision to directly enter the industrial world